Karamunting Fruit Gel as a Natural Dental Plaque Disclosing Solution - Silvia Prasetyowati; M. Ibraar Ayatullah; Sunomo Hadi (Journal of Public Health and Pharmacy)
Introduction: Dental and oral health issues remain a global challenge, with rising dental caries cases, particularly in regions like Sub-Saharan Africa and Indonesia, where 57.6% of the population is affected. Among Indonesian children aged 3-9, caries and toothache are prevalent, highlighting the need for early plaque detection and targeted interventions. This study aims to evaluate the effectiveness of disclosing solution gel formulated from Karamunting fruit (Melastoma malabathricum L.) as a dental plaque identifier in children attending the Special Education School under the Surabaya Foundation for Children with Disabilities.